2014
DOI: 10.1021/ma5010919
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Polymerization of Norbornene Derivatives in the Presence of Boranes

Abstract: Cationic polymerization of 5-methylene-2norbornene, 5-ethylidene-2-norbornene, 5-vinyl-2-norbornene, dicyclopentadiene, and norbornadiene-2,5 in the presence of boranes was systematically studied. It was found that B(C 6 F 5 ) 3 in combination with caprylic acid, 1-phenylethanol or water was a highly active catalyst for the polymerization of 5-alkylidene-2norbornenes. The corresponding cationic polymers were obtained with up to yields 95% and with high molecular weights (M w ≤ 430 000). The activity of 5-alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 70 publications
0
53
0
Order By: Relevance
“…These directions of DCPD transformations, unlike metathesis polymerization, will lead to polymers with saturated and more rigid main chains. Cationic polymerization of DCPD resulted in only low molecular weight polymer products or oligomers . In contrast to this, addition polymerization of DCPD is a more thermodynamically favorable process.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…These directions of DCPD transformations, unlike metathesis polymerization, will lead to polymers with saturated and more rigid main chains. Cationic polymerization of DCPD resulted in only low molecular weight polymer products or oligomers . In contrast to this, addition polymerization of DCPD is a more thermodynamically favorable process.…”
Section: Introductionmentioning
confidence: 82%
“…Norbornene and its derivatives are an unusual class of monomers that can be polymerized by various mechanisms forming polymers with different structures of main chains and properties . This feature, along with the ability to synthesize series of norbornenes with a regularly varying structure, has made these compounds attractive for the macromolecular design of polymers with desired properties and for the systematic study of the relationships “polymer structure‐properties.” Depending on the nature of the side substituents and the structure of the main chain, norbornene‐based polymers can have attractive optical properties, low moisture absorption, thermal and chemical stabilities, promising membrane characteristics, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…74) [318]; (7) a tris(norbornenecarboxylate) connected to a carbon nanotube [319]; (8) bis(norbornenecarboxylate ester)s (e.g. 73) [320]; (9) 5-ethylidenenorbornene (68) [321], including its use as a part of a self-healing system [322]; (10) vinylnorbornene [323]; (11) tetracyclododecene (69) [324]; (12) norbornadienes connected to various hydrophobic groups, including a steroid system [325]; (13) dicyclopentadiene [326,327,328,329,330,331,332,333,334,335,336], including polymerizations performed in the presence zinc oxide nanoparticles [337], urea formaldehyde microcapsules [338],mildly oxidized graphene oxide [339], barium titanate [340], and high internal phase emulsions [341,342]; (14) the norbornadiene-anthracene Diels-Alder adduct (76) [343,344]; (15) norbornenedicarboxylate esters connected to cyanobiphenyl groups [345], to anthracene groups [346], and to nitroxide groups (e.g. 79) [347]; (16) the three stereoisomeric dimethyl norbornenedicarboxylates (determination of the relative rates of ROMP) [348]; …”
Section: Polymerization Reactionsmentioning
confidence: 99%
“…Norbornenes are unique monomers which could be polymerized via different routes to give polymers with various backbones [1][2][3][4]. It has been recently shown that among norbornene derevatives exo-tricyclononenes were more attractive due to their enhanced activities in polymerization [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%